Patch Map for Fast Texture Synthesis - Xiong Changzhen; Guo Fenhong; Zou Jiancheng; Qi Dongxu (2007 IEEE Pacific Rim Conference on Communications, Computers and Signal Processing, 2007)
A novel texture synthesis method is presented to form large and feature-preserved textures. The task of texture synthesis is divided into two phases: analysis, and synthesis. During the analysis phase, we generate a patch map via Graph cuts, feature deformation and matching. The main task of synthesis phase is to pick up a patch in the patch map and place it in the output to synthesize large target textures. The experimental results show that the patch map algorithm fast synthesizes high-quality textures ranging from regular to stochastic. Compared with the existing methods, our approach preserves texture feature well when pixel-based jump map algorithm and graph cuts method fail to produce good results.